The Productivity of Kejobong and Bligon Goats, a Local Indonesian Goats Kept by Farmers - I. Gede Suparta, Budisatria (2012)
This paper discusses the productivity of Kejobong and Bligon goatskept by farmers at traditional management. One farm research was conducted for 12 months at the two farmers group in Central Java and Yogyakarta Provinces. 70 farmers and their goats were monitored, including services per conception, gestation period, litter size, birth weight, postpartum mating, mortality, weaning weight, average daily gain, kidding intervals, kid crop, doe reproduction index and doe productivity. Service per conception, gestation period and postpartum mating of Kejobong goats was higher (p<0.01) than Bligon goats, while litter size did not significantly differ. Birth weight and pre-weaning mortality of Kejobong and Bligon goats was the same, while weaning weight and average daily gain were significantly higher (p<0.05) in Kejobong kids rather than Bligon kids. Kejobong goats had a potentially better performances in terms of growth, feed intake and feed efficiency compared to Bligon goats, however, poor management in terms of feed quality offered by the farmers make those potential was un-emerged, low reproductive performance of Kejobong does. Key Words: Kejobong and Bligon goats, Productivity, Farmers